Analisis Produk, Harga, Pelayanan, dan Digital Marketing terhadap Kepuasan Konsumen dan Dampaknya pada Loyalitas Pelanggan PT Control Systems – Emerson Micromotion Flowmeter - Suharyono Suharyono; Heru Widiyanto (FOCUS, 2021)
This study analyzes products, prices, services, and digital marketing on customer satisfaction and its impact on customer loyalty at PT Control Systems-Emerson Micromotion Flowmeter. This study uses a survey method by distributing questionnaires to PT Control Systems customers as respondents. The quantitative research method uses technical analysis of structural equation modeling (SEM) with AMOS 22 applications. This study uses a sample of 120 respondents. The results showed that products, prices, services, and digital marketing had a positive and significant effect on customer satisfaction and had a positive and significant impact on customer loyalty.